Bruno Latour, um pensador amoderno - Sousa, Leonardo Santos (2015)
This work is mainly aimed to investigate the associations of non-human and human in the composition of the collective philosophical bias contained in latourianas works: Type of Policy: How do science in democracy and Pandora's Hope: Essays on the reality of studies scientific. Having two specific objectives: to discuss the influence of political ecology Latourian the progressive composition of the team and investigate the contributions of relativistic empiricism, in order to have the understanding of scientific practices nowadays. We realize that Bruno Latour has built a relativist empiricism that, in general, rejects the separation between the ontological entities Nature and Culture as well as the separation between subject and object. All efforts are concentrated into question the idea of having a rigid separation between nature and society. The Latourian proposal, contained in amoderno agreement seeks to establish the exercise of the full dialogue between things and the other actors; and thereby defines the anthropocentric power in scientific practices, that democracy requires the political participation of all surfactants, since the proposals articulated in the collective are not derived solely from the logocentrism; but are engendered by / in the plots woven by humans and nonhumans. We realized that the iconoclastic gesture of modern, with which separated the collective in two dimensions: nature on one side and society on the other, was inefficient, why this split happened not because of the proliferation of hybrids on the way these dimensions, the mediation work. We can see that things are not silent, neither are subordinated to the logocentric authoritarianism of humans, even though their voices seem inaudible, things speak, weave well articulated propositions in parliament of things, as a way of composing the common world.